Bonding-site dependence of surface resistivity: CO on epitaxial Cu(100) films. - Tobin, Roger G.; Chang, Liu. (Tufts University. Tisch Library., 2017)
The authors have measured the contribution of CO adsorbed on different bonding sites to the resistivity of epitaxial Cu(100) films. Through an analysis of the correlation between surface resistivity and temperature-programed desorption measurements, CO on terraces is found to affect the resistance much more strongly than CO on defect sites. Two possible explanations are considered: a reduced scattering cross section of defect CO owing to the different local electronic structure at defect sites or strong scattering by the bare defect that is not significantly affected by the adsorption of CO.